The extent and composition of automatic stabilization in EU countries - David P. Coady; Silvia De Poli; Adrian Hernández; Andrea Papini; Alberto Tumino (European Commission, Joint Research Centre (JRC), 2023)
This paper analyses the magnitude of automatic income and demand stabilization in EU Member States between 2011 to 2019. Our analysis finds that automatic income stabilization in 2019 averaged 41.3 percent at the EU level, with considerable variation among Member States. While the extent of stabilization is similar across income groups within countries, the source of stabilization differs, with income taxation (transfers) being more important for high-income (low-income) households. Income stabilization proved stable over time, with a few exceptions driven by major reforms. EU-level demand stabilization averaged 84.7 percent, increasing with household income and reflecting the greater ability of richer households to smooth consumption.
Keywords: H20; E62; E63; 330; Income stabilization; Demand stabilization; Euromod